Bacterial contamination and its Susceptibility in intensive care unit in Thi-qar province / Iraq - Nasser, Nazar (University of Thi-Qar Journal of Science, 2013)
To identify the cause and the source of bacterial infection among patients of intensive careunit this study had been conducted in Al-Imam Al-Hussein hospital in Thi-qar province for the period from 1st September to end of December 2011 .A total of 320 swabs and samples were collected from 17 different sites of Intensive Care Unitenvironment and inoculated on a normal cultural media ,then incubated at 37OC for 24 hour . The growth revealed different bacterial colonies which had been tested for their morphological and biochemical characteristics. Sixty eight of pure isolates were obtained including 24 (35.29%) Gram positive bacterial isolates, 44(64.71%) of Gram negative bacterial isolates, the highest rates (19.11%) of bacterial contamination had been found on the walls and the floor . Sensitivity tests for all isolates were done using 25 types of commonly used antibiotics in Iraq, the results revealed that the genus Enterobacter spp. had a high resistance as a Gram negative bacteria, and Staphylococcus spp. had a high resistance as a Gram positive bacteria to most of the tested antibiotics, MIC tests for 5 types of antibiotics were applied on the most resistant and the most sensitive isolates which reflect that all isolates have a low rate of MIC against Ciprofloxacin .